2020
DOI: 10.1055/a-1205-1021
|View full text |Cite
|
Sign up to set email alerts
|

Der Zugang zu gesundheitlicher Versorgung nach Einführung der elektronischen Gesundheitskarte: die Sicht geflüchteter Patient(inn)en

Abstract: Zusammenfassung Ziel der Studie Der Zugang zur gesundheitlichen Versorgung für Geflüchtete wird bundesweit in den Kommunen unterschiedlich organisiert, sowohl im Hinblick auf die Organisation von (sozialarbeiterischen bzw. kommunalen) Unterstützungsangeboten als auch durch die Wahl des Zugangsmodells (elektronische Gesundheitskarte/eGK-Modell oder Behandlungsschein/BHS-Modell). In den letzten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 22 publications
1
2
0
3
Order By: Relevance
“…In addition, the results show parallels to studies on refugees from other countries of origin in Germany, e.g. persisting communication problems [21,22].…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…In addition, the results show parallels to studies on refugees from other countries of origin in Germany, e.g. persisting communication problems [21,22].…”
Section: Discussionsupporting
confidence: 77%
“…None of our interviewees received information about the German healthcare system or healthcare in general through official channels. The fact that information about the health care system is often obtained via informal channels is also reported in other (inter-)national studies [22,27]. This should be changed urgently to improve care and facilitate access for the refugees.…”
Section: Information and Support Needsmentioning
confidence: 83%
“…However, regulations vary across German federal states, with some states like Bremen and Hamburg issuing an electronic health cards immediately upon arrival, eliminating the need for treatment certificates (Gottlieb and Schülle, 2021). This immediate access facilitates health care utilization, particularly for refugees with greater health care needs and leads to increased visits to outpatient clinics (Claassen and Jäger, 2018; Rolke et al , 2020). Consistently, participants in our study who had received an electronic health card found it easier to use compared with treatment certificates.…”
Section: Discussionmentioning
confidence: 99%
“…Die Abrechnung erfolgt analog zu gesetzlich krankenversicherten Patient/-innen mit der Krankenkasse, die sich die ausgelegten Kosten dann vom zuständigen Sozialamt erstatten lässt. In diesem Modell sind die logistischen Barrieren im Zugang zu medizinischer Versorgung am niedrigsten [ 35 , 36 ] und die Verwaltungskosten am geringsten [ 24 ].…”
Section: Determinanten Der Gesundheit Und Medizinischen Versorgung Vo...unclassified